Functional determination of site-mutations in rdxA involved in metronidazole resistance of Helicobacter pylori - Huang, Jia; Li, Zhiyu; Ge, Fulin; Sun, Chao; Deng, Zixin; Yao, Weiyan; He, Xinyi (Frontiers in Cell and Developmental Biology, 2024)
Background: Metronidazole (MTZ) is among the first-line drugs against the human gastric pathogen Helicobacter pylori (H. pyloriHp). MTZ is used as a prodrug that is activated by an oxygen-insensitive enzyme NADPH nitroreductase (RdxA). Loss-offunction mutations in rdxA make H. pyloriHp MTZ resistant; however, experimental proof is lacking.: We collected 139 gastric biopsy samples from patients suspected of H. pyloriHp infection in Shanghai, and amplified Hp-specific rdxA gene from 134 samples. All these rdxA genes were sequenced and phylogenetically compared. The effect of mutations on RdxA function was measured by expressing them in E. coli DH5α by using the MTZ sensitivity test. Results: In total, 134 gastric biopsy samples were identified as H. pyloriHp positive. Of the 134 samples, 74 and 6 had point mutations at the various sites or promoter region of rdxA, generating truncated and extended fused proteins, respectively. The remaining 54 were full-length with single nucleotide variation (SNV) compared with the wild-type RdxA from H. pyloriHp, with 49 clustering with hpEastAsia, 3 with hpEurope, and 2 with hpNEAfrica. All 134 rdxA were expressed in E. coli DH5α; 22 and 112 resultant strains showed MTZ-sensitive and MTZ-resistant phenotypes, respectively. Comparative analysis of single nucleotide polymorphisms (SNPs) in the functional and inactivated RdxA revealed 14 novel mutations in RdxA, 5 of which conferred MTZ resistance: S18F, D59S, L62I, S79N, and A187V. Conclusion: The occurrence of MTZ resistance induced by site-mutation of RdxA in patients with H. pylori Hp infection was 83.6% (112/134) in the Shanghai region. The major form of loss-of-function mutation was truncation of RdxA translation at a rate of 58/112 (51.8%). Molecular detection reliably determined the resistance of H. pyloriHp to MTZ. Thus, the functional mutants involved in MTZ resistance facilitate clinical diagnosis and medication based on sequence analysis.